2019
DOI: 10.1080/01441647.2019.1575491
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the distances people walk to access public transport

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 53 publications
0
33
0
1
Order By: Relevance
“…Moreover, we were unable to obtain conclusive results on the influence of variables related to the accessibility to and from public transport and street density, due to the limitations presented by the indicators chosen for them. Previous research on the key factors that influence the relationship between walking and transit could help derive indicators to measure the distance people walk to and from public transport [73]. For example, the effect of street density is different depending on the type of urban fabric formed by these streets, either traditional grid street patterns or suburban neighbourhood design.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we were unable to obtain conclusive results on the influence of variables related to the accessibility to and from public transport and street density, due to the limitations presented by the indicators chosen for them. Previous research on the key factors that influence the relationship between walking and transit could help derive indicators to measure the distance people walk to and from public transport [73]. For example, the effect of street density is different depending on the type of urban fabric formed by these streets, either traditional grid street patterns or suburban neighbourhood design.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2017) [36] reviewed the development and application of deficit function modelling in PT and indicated that graphical deficit function concepts are conducive to PT planning and operations. Soest et al (2020) [37] discussed how walking relates to the use of PT and indicated that further empirical research on the influences of culture and climate in different geographical areas is needed.…”
Section: Public Transportationmentioning
confidence: 99%
“…Based on Formulas (37) and 50, the individual value of the passenger for the energy factor during the time period t 1 ∼ t m can be calculated by Formula (52):…”
Section: Driver Utility Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, developing a computational framework based on smartphone data has proved to provide more accurate measurement of the observed traveled distances, leading to better estimation of potential emissions reductions with computed alternatives [56,57]. In addition, the use of smartphone data has been shown to provide a better estimation of observed walking for PT access/egress, leading to better estimations of potential changes in physical activity with mode shift [27,60,61]. Despite these computational potentials, most of the previous literature has studied the reduced emissions and increased travel times separately [55,62], focusing on comparing alternatives such as bike, PT, or shared bike [18,63].…”
Section: Introductionmentioning
confidence: 99%